The Effect Of Dolomite As Lightweight Agregate’s Substitute To The Concrete’s Compressive Strength - Budio, Sugeng P.; Nurlina, Siti; Ristinah, Ristinah; Hidayat, M. Taufik; Nuralinah, Devi; Permana, Andrian (Rekayasa Sipil, 2013)
Indonesia is the country which has many natural resources that can be utilized in everyday life. One of the uses of natural resources is as a construction material. Human life cannot be separated from the construction field, because house is one of the basic human needs. Dolomite is a natural resource, which is generally used by many people as a mixture of cement, bricks, and soil fertilizer. However further research in the use of dolomite as a natural resource is needed, so that it is more useful and save. Dolomite can be used as a substitute for sand in concrete construction. Therefore, this research is conducted on the use of the dolomite material in the construction of concrete. Concrete specimens were made with a mixture proportion of dolomite as a replacement of sand. Then the compressive strength test is conducted. From these tests, it can be seen the influence of dolomite in the concrete mix and the percentage content of dolomite that can be used instead of sand.Â